Neocentromeres in 15q24-26 Map to Duplicons Which Flanked an Ancestral Centromere in 15q25 - Ventura, Mario (Cold Spring Harbor Laboratory Press, 2003)
The existence of latent centromeres has been proposed as a possible explanation for the ectopic emergence of neocentromeres in humans. This hypothesis predicts an association between the position of neocentromeres and the position of ancient centromeres inactivated during karyotypic evolution. Human chromosomal region 15q24-26 is one of several hotspots where multiple cases of neocentromere emergence have been reported, and it harbors a high density of chromosome-specific duplicons, rearrangements of which have been implicated as a susceptibility factor for panic and phobic disorders with joint laxity. We investigated the evolutionary history of this region in primates and found that it contains the site of an ancestral centromere which became inactivated about 25 million years ago, after great apes/Old World monkeys diverged. This inactivation has followed a noncentromeric chromosomal fission of an ancestral chromosome which gave rise to phylogenetic chromosomes XIV and XV in human and great apes. Detailed mapping of the ancient centromere and two neocentromeres in 15q24-26 has established that the neocentromere domains map approximately 8 Mb proximal and 1.5 Mb distal of the ancestral centromeric region, but that all three map within 500 kb of duplicons, copies of which flank the centromere in Old World Monkey species. This suggests that the association between neocentromere and ancestral centromere position on this chromosome may be due to the persistence of recombinogenic duplications accrued within the ancient pericentromere, rather than the retention of “centromere-competent” sequences per se. The high frequency of neocentromere emergence in the 15q24-26 region and the high density of clinically important duplicons are, therefore, understandable in the light of the evolutionary history of this region.